2014
DOI: 10.3109/08916934.2014.938320
|View full text |Cite
|
Sign up to set email alerts
|

The defective bone marrow-derived mesenchymal stem cells in patients with chronic immune thrombocytopenia

Abstract: Chronic immune thrombocytopenia (ITP) is characterized by autoimmune-mediated platelet destruction and impairment of thrombopoiesis. Mesenchymal stem cells (MSCs) are proposed to exhibit immune modulatory functions in self-tolerance maintenance. In this study, we aimed to characterize phenotypically and functionally bone marrow (BM)-derived MSCs from adult chronic ITP patients. Our results showed that BM-MSCs from patients with chronic ITP exhibited impaired proliferation, abnormal morphology and excessive apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 54 publications
1
37
0
Order By: Relevance
“…Our previous study (Zhang et al , ) showed that MSCs from ITP patients displayed enhanced senescence and apoptosis and showed a lower capacity for inhibiting the proliferation of activated T cells, inducing regulatory T cells (Tregs) and suppressing the synthesis of anti‐glycoprotein (GP)IIb‐IIIa antibodies. Thus, it was confirmed that BM‐MSCs were defective in chronic ITP patients (Zhang et al , ).…”
mentioning
confidence: 76%
“…Our previous study (Zhang et al , ) showed that MSCs from ITP patients displayed enhanced senescence and apoptosis and showed a lower capacity for inhibiting the proliferation of activated T cells, inducing regulatory T cells (Tregs) and suppressing the synthesis of anti‐glycoprotein (GP)IIb‐IIIa antibodies. Thus, it was confirmed that BM‐MSCs were defective in chronic ITP patients (Zhang et al , ).…”
mentioning
confidence: 76%
“…The reason for the decreased number of Ts cells is currently unknown. We speculated that decreased plasma IL10 and TGFB1 concentrations and the impaired immune regulated ability of bone marrow‐derived mesenchymal stem cells could, at least, partly explain the reasons (Andersson et al , ; Zhang et al , ). Consistent with the literature, we also found a positive correlation between age and the percentage of CD8 + CD28 − Ts cells in controls but not in ITP patients (Bandres et al , ; Vallejo, ).…”
Section: Discussionmentioning
confidence: 99%
“…This will increase patient willingness to get free of steroids when possible, helping physician to limit the continuum damage accrual of SLE patients. References: [1] …”
Section: Disclosure Of Interestmentioning
confidence: 99%
“…The use of corticosteroids (CS) increases the risk of osteoporosis induced by corticosteroid (GIOP) and FF [1]. Denosumab is monoclonal antibody that binds to RANKL, inhibiting osteoclast formation and activation, used for both male and women OP to prevent FFx [2,3].…”
Section: Introductionmentioning
confidence: 99%